SUPPORTING ONLINE LEARNING IN THE COUNTRYSIDE - Ergasheva Mukhlisa (American Journals, 2023)
This article describes the effectiveness and challenges of online learning in rural areas. The findings of the study reveal that e-learning is a huge challenge for rural schools with a lack of online learning resources, skilled teachers, and so on.
Keywords: Rural region, online learning, lack of equipment, internet, education.